DEVELOPING FINANCIAL LITERACY AMONG STUDENTS OF SMK TELKOM JAKARTA - Rahmadi, Rahmadi; Natali, Yus; Cahyadi, Nanang; Hafiza, Lia; Sularso, Alva Nurvina (PT. Altin Riset Publishing, 2024)
This community service aims to provide an understanding of effective financial management for students of SMK Telkom Jakarta. Students who are now included in the so-called Generation Z face considerable challenges. Starting from labor market competition to financial problems. So students must be equipped with additional skills for their financial management from an early age. In this activity, we apply the Workshop and Practical Training method. Workshop by providing basic knowledge about financial management. And practical training with the Kakeibo method (traditional Japanese method for managing finances). The results of this activity have an impact on students to care more about their finances, namely increasing financial awareness, and adopting good habits such as recording personal income and expenses.